Geochemistry of dike rocks of the Argentine Islands and the near area of the Antarctic Peninsula (Western Antractica) - Artemenko, G.V. (Reports of the National Academy of Sciences of Ukraine, 2018)
The dike rocks in the area of the Argentine Islands and the near part of the Antarctic Peninsula by geochemical characteristics are mature island-arc matter of calc-alkaline formations that were formed moderate depths due to the melting of a metasomatic mantle source. The primitive (outgoing) melts are, probably, close by the composition to high-magnesium dike rocks. Variations in the composition of dike basites can be associa ted with the fractional crystallization with clinopyroxene admixtures dominant in liquidase to ∼ 5% by weight, and after — plagioclase, hornblende, and ore minerals (probably, titanomagntite). The products of deep mantle (plum) sources in the selected samples were not detected.